PREPARATION AND PARTICIPATION IN THE 2024 ELECTION OF THE REGENT AND DEPUTY REGENT OF SOUTHEAST ACEH REGENCY IN BAMBEL DISTRICT - Muhammad Harpandi; Abu Sahrin (Program Pascasarjana UIN Sumatera Utara, 2025)
This study is to analyze the methods of preparation and extent of community involvement in the implementation of the Regent and Deputy Regent elections in Southeast Aceh Regency, specifically in Bambel District, in 2024. Regional head elections are a fundamental component of the democratic framework, where active community participation serves as a measure of the efficacy of the democratic process at the local level. This research employs a qualitative methodology using descriptive techniques, including in-depth interviews, observations, and documentation analysis involving election organizers, community leaders, and voters. The study's findings demonstrate that the Independent Election Commission (KIP) and the District Election Committee (PPK) have executed their preparations in accordance with the prescribed steps, despite many technical and social challenges. Meanwhile, community participation shows a positive trend, driven by increased political awareness and the active role of traditional and religious leaders in encouraging residents to exercise their right to vote. However, there are still challenges in the form of apathy among some young voters and the influence of money politics. This study recommends the need to strengthen local-based political education to improve the quality of voter participation in the future.